Filozofia – autonomia i dominacja - Tyl, Mirosław (Człowiek i Społeczeństwo, 2022)
The purpose of the paper is take a look from the perspective of the field theory of Pierre Bourdieu at the history of the Polish post-war philosophy with special attention given to the so-called Christian philosophy. In reference to Bourdieu’s research practice, the author postulates application of research strategies of the sociology of science/philosophy to historical and philosophical studies with a belief that they enhance the picture of philosophical dynamics of the past. From this point of view, the author focuses on relations between the field of Christian philosophy and the field of church authority, exposing the issue of philosophy’s autonomy.